Comparative Efficacy and Safety of Weekly GLP-1/GIP Agonists vs. Weekly Insulin in Type 2 Diabetes: A Network Meta-Analysis of Randomized Controlled Trials - Hazem Ayesh; Sajida Suhail; Suhail Ayesh; Kevin Niswender (Biomedicines)
Background: Diabetes mellitus (DM) significantly impacts global health due to its complications and the economic burden it places on healthcare systems. The rise of novel once-weekly diabetes medications with different mechanisms of action necessitates an evaluation of their relative efficacy and safety. Objectives: This study compares the efficacy and tolerability of once-weekly insulin analogs (icodec and BIF) with once-weekly GLP-1/GIP agonists (semaglutide, exenatide, tirzepatide, dulaglutide) in managing type 2 diabetes mellitus (T2DM). Methods: We conducted a network meta-analysis (NMA) using data from randomized controlled trials (RCTs) that compared these treatments with a baseline of daily basal insulin. Primary outcomes included changes in HbA1c, body weight, and tolerability. Results: The analysis integrated data from 25 RCTs, involving 18,257 patients. Tirzepatide significantly outperformed other treatments in reducing HbA1c and promoting weight loss. Weekly insulins, compared to GLP-1/GIP agonists, showed a more tolerable profile and were beneficial for certain patient demographics emphasizing weight stability. Conclusion: Our findings suggest that while once-weekly GLP-1/GIP agonists provide superior glycemic control and weight management, weekly insulins offer viable options for patients prioritizing fewer side effects and weight stability. This comprehensive comparison aids in refining personalized treatment strategies for T2DM management.